2017
DOI: 10.1155/2017/7942531
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Effect of Lactulose on a Methotrexate-Induced Liver Injury Model

Abstract: The most severe side effect of prolonged MTX treatment is hepatotoxicity. The aim of this study is to investigate the effect of lactulose treatment on MTX-induced hepatotoxicity in a rat model. Twenty-four male rats were included in the study. Sixteen rats were given a single dose of 20 mg/kg MTX to induce liver injury. Eight rats were given no drugs. 16 MTX-given rats were divided into two equal groups. Group 1 subjects were given lactulose 5 g/kg/day, and group 2 subjects were given saline 1 ml/kg/day for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…These doses are necessary for rats to account for their faster drug metabolism, which can easily exceed that of a human by a multiple of ≥10. The MTX dose that we choose for our study can be seen from some previous studies [ 13 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…These doses are necessary for rats to account for their faster drug metabolism, which can easily exceed that of a human by a multiple of ≥10. The MTX dose that we choose for our study can be seen from some previous studies [ 13 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our investigation, we used the published data (5,6) for the anatomical peculiarities and topography of the studied organs in the rabbit for better orientation. This study is a continuation of the previous study for the rabbit glands (6) and deepens the knowledge for these glands, because it is focused on the macrometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate is typically well tolerated by patients and still the first choice as the cost effective and well-experienced treatment option (5). It has many application fields as a therapeutic agent at low doses in autoimmune diseases and at high doses in many malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is one of the important causes of liver cell damage, and it is known that endotoxin is the second blow to CLI and induces chronic liver disease progression via gut-liver axis [ 36 , 37 ] and directly damage liver cells and induce hepatocyte apoptosis [ 38 , 39 ]. Preclinical evidence showed that LA reduced liver injury and decreased oxidative stress response, excessive inflammatory response, and fibrotic progression via downregulating endotoxin levels [ 40 , 41 ]. Therefore, LA was used as positive control in the present study.…”
Section: Discussionmentioning
confidence: 99%